The Relevance of The Independent Learning Curriculum to the 21st Century Learning Model in Development of Society Era 5.0 - Limbong, Ezra Egidia Shelomita; Pasaribu, Shofia Debora; Tampubolon, Yenji Betaria Sonata; Lubis, Rajo Hasim (EDUCTUM: Journal Research, 2024)
Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations that were born in the era of the industrial revolution 4.0, such as the internet of things (internet for everything), artificial intelligence (artificial intelligence), Bit Data (large amounts of data), and robots to improve the quality of human life. This era is a new opportunity and challenge for students to improve their soft skills as preparation for the future. It is generally known that the curriculum is the "soul" of education. The curriculum should need to be evaluated dynamically and periodically following current developments, especially science and technology. The curriculum is also prepared taking into account the competencies needed by society and graduates. Kukirikulm independent learning is one of the new policies of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia (Kemendikbudristek RI) which is aimed at realizing an innovative learning process and following the needs of students (Student-Centered). The era of society 5.0 takes place in the 21st century, which is the glory of the digital world. An innovative learning model is an approach or learning method that uses new, creative ways and prioritizes critical thinking, active involvement and active participation of students in the learning process with the aim of developing students' ability to think independently, creatively and innovatively, so that they can generate new ideas, solve problems, and apply knowledge in real life. Innovative learning models are very relevant in the Merdeka Curriculum because the Merdeka Curriculum emphasizes a studentcentered learning approach, which prioritizes creativity, collaboration and problem-solving abilities. Innovative learning models such as project-based learning, problem-based learning, or technology-based learning can help realize these goals by providing interesting and relevant learning experiences for students.